Theoretical analysis of absorption chiller system - Mohd Hafeez, Alias (2010)
Absorption chiller is a cooling system that uses heat instead of electricity to cool something. The different types of absorption chillers are solar, water, gas, and bromide with steam. The process to cool a building with an absorption chiller is similar to that used by conventional air conditioning systems in that there is compressor, condenser, and evaporator equipment within the system. Refrigerant, normally lithium bromide is subjected to pressure and builds up heat in the compressor. As the pressure and heat build, the liquid is converted to a vapor gas. The gas then moves to the condenser where the heat dissipates and it is turned back into a liquid. The cooled liquid is directed into the evaporator, where it turns into a gas and pulls heat from the air; fan blowers send the cool air into the building. The gas moves from the evaporator into the compressor and the process starts again. In traditional air conditioning systems, this process is achieved with the use of an electric powered pump. In a gas absorption chiller, the pump is run by a natural gas line attached to the system. When the system is powered on, the natural gas activates the pump to flow refrigerant through the compressor. These systems run more efficiently than electric air conditioning systems but are still more costly to operate than solar varieties. In areas where sunlight is not available for extended periods of time, a gas absorption chiller is more often used. As we know that the COP of absorption chiller is low to be compared with the refrigerant system. This problem actually can be resolved by doing an analysis and a study of each component in the absorption chiller especially the condenser that plays the main role to remove heat from the system. It will be a good system if the condenser can remove heat as much as possible. Normally, we will use a forced type of air condenser which uses a fan to blow out the heated air from the system. It also the same with an evaporator but differently functions as the evaporator has a great capacity when the temperature differences between outlet and inlet is high. Talking about capacity, it surely will relate to resistance in the evaporator. The metal is known to offer less resistance but it actually depends on what type of refrigerant we are going to use. Iron and steel are very suitable for ammonia while brass and copper are for the other type of refrigerant. It is very important to have a high velocity for the flow of refrigerant and fluid over the evaporator. For the generator, it is an energy source for the absorption chiller system and usually the direct flow and heat pipe evacuated tube collector solar will be used as the generator because of their potential and efficiencies even though it is the reason why the absorption is highly cost. To determine the efficiency of a system, it can be shown by a COP for the system. For new condenser concept will lowering the condensing temperature. Hence the cooling capacity will increased. So it could enable the compressor to operate at higher load for more longer time. Other than that, chiller with higher cooling capacity could carry a higher loads with higher COP.